Ballad of an American : a graphic biography of Paul Robeson - Rudahl, Sharon (Rutgers University Press, 2020)
"The first-ever graphic biography of Paul Robeson, Ballad of an American, charts Robeson's career as a singer, actor, scholar, athlete, and activist who achieved global fame. Through his films, concerts, and records, he became a potent symbol representing the promise of a multicultural, multiracial American democracy at a time when, despite his stardom, he was denied personal access to his many audiences. Robeson was a major figure in the rise of anti-colonialism in Africa and elsewhere, and a tireless campaigner for internationalism, peace, and human rights. Later in life, he embraced the civil rights and antiwar movements with the hope that new generations would attain his ideals of a peaceful and abundant world. Ballad of an American features beautifully drawn chapters by artist Sharon Rudahl, a compelling narrative about his life, and an afterword on the lasting impact of Robeson's work in both the arts and politics. This graphic biography will enable all kinds of readers-especially newer generations who may be unfamiliar with him-to understand his life's story and everlasting global significance. Ballad of an American: A Graphic Biography of Paul Robeson is published in conjunction with Rutgers University's centennial commemoration of Robeson's 1919 graduation from the university"--